The virgin of Guadalupe and the conversos : uncovering hidden influences from Spain to Mexico - Hernández, Marie Theresa, 1952- (New Brunswick, New Jersey : Rutgers University Press, 2014)
Hidden lives, hidden history, and hidden manuscripts. In The Virgin of Guadalupe and the Conversos, Marie-Theresa Hernández unmasks the secret lives of conversos and judaizantes and their likely influence on the Catholic Church in the New World. The terms converso and judaizante are often used for descendants of Spanish Jews (the Sephardi, or Sefarditas as they are sometimes called), who converted under duress to Christianity in the fourteenth and fifteenth centuries. There are few, if any, archival documents that prove the existence of judaizantes after the Spanish expulsion of the Jews in 149.
Virgin of the secret river -- The monks of the king: Los Monjes del Rey -- Divine splendor -- Hebrew truth: Hebraica veritas -- The sphinx -- Miguel sánchez, Guadalupe, and the inquisition -- Madre Sion.
Includes bibliographical references (pages 229-243) and index.
Print version record.
English.
JSTOR
Keywords: Espinosa de los Monteros, Manuel, -- 1773-1838.; Carvajal, Luis de, -- 1567?-1596.; Carvajal, Luis de, -- 1567?-1596; Espinosa de los Monteros, Manuel, -- 1773-1838; Christianity and other religions -- Judaism; Judaism -- Relations -- Christianity; Crypto-Jews -- Mexico -- History -- 18th century; Crypto-Jews -- Mexico -- History -- 19th century; Guadalupe, Our Lady of; Christianisme -- Relations -- Judaïsme.; Judaïsme -- Relations -- Christianisme; Cryptojuifs -- Mexique -- Histoire -- 18e siècle.; Cryptojuifs -- Mexique -- Histoire -- 19e siècle.; Nuestra Señora de Guadalupe; RELIGION -- Christian Life -- Social Issues; RELIGION -- Christianity -- General; LITERARY CRITICISM -- European -- Spanish & Portuguese; Christianity; Crypto-Jews; Guadalupe, Our Lady of; Interfaith relations; Judaism; Mexico; 1700-1899; History